Unpacking Culture: Art and Commodity in Colonial and Postcolonial Worlds - Phillips, Ruth B.; Steiner, Christopher Burghard (University of California Press, 1999)
Tourist art production is a global phenomenon and is increasingly recognized as an important and authentic expression of indigenous visual traditions. These thoughtful, engaging essays provide a comparative perspective on the history, character, and impact of tourist art in colonized societies in three areas of the world: Africa, Oceania, and North America. Ranging broadly historically and geographically, Unpacking Culture is the first collection to bring together substantial case studies on this topic from around the world.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé